2018
DOI: 10.1093/glycob/cwy014
|View full text |Cite
|
Sign up to set email alerts
|

Variant in human POFUT1 reduces enzymatic activity and likely causes a recessive microcephaly, global developmental delay with cardiac and vascular features

Abstract: Protein O-fucosyltransferase-1 (POFUT1) adds O-fucose monosaccharides to epidermal growth factor-like (EGF) repeats found on approximately 100 mammalian proteins, including Notch receptors. Haploinsufficiency of POFUT1 has been linked to adult-onset Dowling Degos Disease (DDD) with hyperpigmentation defects. Homozygous deletion of mouse Pofut1 results in embryonic lethality with severe Notch-like phenotypes including defects in somitogenesis, cardiogenesis, vasculogenesis and neurogenesis, but the extent to wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…The pSecTag2c-based N-terminally 6xHis-tagged human POFUT1 lacking C-terminal RDEF sequence expression plasmid was described previously [ 69 ]. The pCMV6-based Myc-DDK-tagged mouse protein O -fructosyltransferase 2 (POFUT2) expression plasmid was purchased from Origene.…”
Section: Methodsmentioning
confidence: 99%
“…The pSecTag2c-based N-terminally 6xHis-tagged human POFUT1 lacking C-terminal RDEF sequence expression plasmid was described previously [ 69 ]. The pCMV6-based Myc-DDK-tagged mouse protein O -fructosyltransferase 2 (POFUT2) expression plasmid was purchased from Origene.…”
Section: Methodsmentioning
confidence: 99%
“…A recently identified heterozygous mutation in POFUT1 , associated with DDD4 is also accompanied by Hidradenitis Suppurativa (HS) which is marked by recurrent painful nodules and abscesses [82]. A homozygous recessive mutation in POFUT1 ablates a N-glycan site and is correlated with more severe developmental defects [83]. However, the loss of the N-glycan is not the basis of the reduced activity of POFUT1.…”
Section: O-fucose Glycansmentioning
confidence: 99%
“…This process is considered to occur in the ER (Luo & Haltiwanger, 2005). Notably, it was recently reported that the p.Ser162Leu mutation of POFUT1 in humans likely causes global developmental delays, such as microcephaly with cardiovascular defects (Takeuchi, Wong, et al, 2018). Additionally, the loss of Pofut1 in mice reportedly causes embryonic lethality due to a global loss of Notch signaling (Shi & Stanley, 2003).…”
Section: O-fucosementioning
confidence: 99%